2018
DOI: 10.1107/s160057671801052x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crystal structure defects on the small-angle neutron scattering/diffraction patterns of clay-rich porous media

Abstract: Analysing the structure and microstructure of compacted swelling clay minerals is important because of the applications of these minerals in engineering and environmental sciences. Given the typical sub-micrometre size of the particles and pores in clays, small-angle scattering techniques are well suited for such analysis. Interpretation of the intensity patterns, however, remains complex, especially in the intermediate region between the first Bragg peak and the smallangle range. In this study, theoretical sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…To estimate the level of anisotropy, an angular average along the principal directions of these 2D scattering patterns is performed using an averaging angle of 15°. A comparison of the two methods is presented in ref 46, showing a very good agreement.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…To estimate the level of anisotropy, an angular average along the principal directions of these 2D scattering patterns is performed using an averaging angle of 15°. A comparison of the two methods is presented in ref 46, showing a very good agreement.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Efforts to characterize the nanoscale structure, energetics, and transport properties of clay–water assemblages are notoriously arduous, in part because these assemblages are stabilized by relatively weak interparticle interactions across nanometer-scale water films. ,, These interactions are highly sensitive to changes in the hydration state, external confining pressure, and aqueous chemistry conditions including salinity and connate counterion identity . Experimental techniques that provide a nanoscale view of minimally disrupted smectite–water assemblages [predominantly X-ray diffraction (XRD), ,, small-angle X-ray scattering (SAXS), and cryogenic transmission electron microscopy (cryo-TEM) ,, ] indicate that they generally consist of relatively complex microstructures involving the coexistence of several stable hydration states, including crystalline hydrates with interclay separations of 0.3, 0.6, or 0.9 nm and osmotic hydrates with interclay separations of ≥3 nm. The crystalline hydrates are thought to be controlled by short-range ion and surface hydration forces in discrete water layers sandwiched between adjacent clay basal surfaces, whereas the osmotic hydrates are thought to reflect a balance of long-range van der Waals and electrostatic interactions between clay nanoparticles. To date, no model has successfully incorporated both osmotic and crystalline hydrates simultaneously to correctly describe the structure, hydraulic permeability, or other properties of hydrated clay assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…I/S smectites in COx betokens for smectite minerals with stable interlayer space (i.e., restrained interlayer osmotic swelling) saturated with Ca and Mg cations (Gaucher et al, 2004). For Ca/Mg saturated smectites in the crystalline swelling regime (accumulation of 1W-3W), molecular dynamics and X-ray diffraction studies demonstrated that for high saturations, the interlayer space ℎ ranges between 1.2-1.8 nm (Sun et al, 2015;Zhang et al, 2016;Ferrage et al, 2018). This will help us initialize the first internal variable ℎ.…”
Section: 1test Descriptionmentioning
confidence: 99%